KDA vs Full Attention Accuracy-Throughput Trade-offs on Long-Sequence GEMM Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: What is the accuracy-throughput trade-off of Kimi Delta Attention (KDA) versus full attention on the GEMM benchmark when processing sequences longer than 8k tokens. 9 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated literature s
Machine-generated literature synthesis.